1995
DOI: 10.1073/pnas.92.26.12190
|View full text |Cite
|
Sign up to set email alerts
|

d-alpha-tocopherol inhibition of vascular smooth muscle cell proliferation occurs at physiological concentrations, correlates with protein kinase C inhibition, and is independent of its antioxidant properties.

Abstract: ABSTRACTd-a-Tocopherol, but not d-jJ-tocopherol, negatively regulates proliferation of vascular smooth muscle cells at physiological concentrations. d-c-Tocopherol inhibits protein kinase C (PKC) activity, whereas d-13-tocopherol is ineffective. Furthermore d-18-tocopherol prevents the inhibition of cell growth and of PKC activity caused by d-ctocopherol. The negative regulation by d-cv-tocopherol of PKC activity appears to be the cause and not the effect of smooth muscle cell growth inhibition. d-a-Tocopherol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
151
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(162 citation statements)
references
References 53 publications
6
151
1
1
Order By: Relevance
“…The combination of ascorbic acid and ␤-tocopherol, an equally strong antioxidant in comparison to ␣-tocopherol but lacking other biological properties present in ␣-tocopherol PKC inhibitory and antiproliferative activities) [28] partially decreased VEGF expression, suggesting that the reduction of oxidative stress is not the only mechanism involved. Since augmented PKC activity has been shown in apoE−/− [29] and PKC activation can upregulate VEGF expression [4], it is conceivable that the observed in vivo effect of ␣-tocopherol on VEGF expression is due to both antioxidant and PKC inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of ascorbic acid and ␤-tocopherol, an equally strong antioxidant in comparison to ␣-tocopherol but lacking other biological properties present in ␣-tocopherol PKC inhibitory and antiproliferative activities) [28] partially decreased VEGF expression, suggesting that the reduction of oxidative stress is not the only mechanism involved. Since augmented PKC activity has been shown in apoE−/− [29] and PKC activation can upregulate VEGF expression [4], it is conceivable that the observed in vivo effect of ␣-tocopherol on VEGF expression is due to both antioxidant and PKC inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…The present study reveals that both d-α-tocopherol and probucol, prevent the high glucose-induced activation of DAG-PKC pathway by enhancing DGK activity in human glomerular mesangial cells, similar to previous reports (9,11). On the other hand, Tasinato et al (19) reported that d-α-tocopherol normalized TPA-induced activation of PKC. However, we show that d-α-tocopherol and probucol do not inhibit TPA-induced PKC activation.…”
Section: Discussionmentioning
confidence: 99%
“…No doubt they are vital cogs in numerous metabolic reactions and are co players in redox homeostasis [21][22][23][24][25] but then are many others cellular molecules of equal importance. Further,many AO perform equally or even more important of non-antioxidant duties [20,26,27].The examples are role of vitamin A in vision [28], vitamin C in collagen synthesis [29][30][31][32][33] and vitamin E in smooth muscle cell proliferation endothelial dysfunction platelet aggregation by a protein kinase C dependent mechanism and tumor suppression [26,[34][35][36].…”
mentioning
confidence: 99%